2021
DOI: 10.20944/preprints202106.0527.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety Leadership and Safety Knowledge-Attitude-Behaviour (KAB) in Malaysia’s Manufacturing SMEs: A Higher Order Two-Stage Approach of PLS-SEM

Abstract: .Most of the accident cases at work are caused by unsafe behaviour. Scholars have thus extensively researched factors of safe behavior.Safety leadership is stated as the most effective factor in safety behaviour. Besides, safety knowledge and safety attitudes are also found to influence safety behaviour. The purpose of this paper is to investigate the nature of the relationship between safety leadership, safety knowledge, safety attitude, and safety behavior, which has been found to be limited or rare in previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Attitudes are crucial in shaping an individual's workplace safety behavior [9]. Safety attitudes refer to an individual's tendency to react positively or negatively toward safety-related objects or situations [10]. The concept of safety attitude represents the workers' attitudes and perceptions regarding safety in the workplace [9,10].…”
Section: Safety Attitudementioning
confidence: 99%
See 2 more Smart Citations
“…Attitudes are crucial in shaping an individual's workplace safety behavior [9]. Safety attitudes refer to an individual's tendency to react positively or negatively toward safety-related objects or situations [10]. The concept of safety attitude represents the workers' attitudes and perceptions regarding safety in the workplace [9,10].…”
Section: Safety Attitudementioning
confidence: 99%
“…Top management should ensure that employees have the necessary awareness and training related to their job responsibilities [11]. Studies have demonstrated that individuals' attitudes toward risk-taking can vary, highlighting the importance of developing strategies considering individual differences [10,11]. Organizations can create a safer workplace and prevent accidents and injuries by promoting a positive safety climate and shaping employees' safety attitudes.…”
Section: Safety Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…Positive safety behavior at the workplace is one of the most essential elements that cannot be taken lightly in an organization [1]. The negligence of positive safety behavior could lead into high accident case at workplace [2,3]. Accident, even if minor, can cause serious adverse effect to the organization [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, in Malaysian settings, supervisor safety roles is found to have insignificant effect towards safety performance in terms of accident and injury reduction [20]. On one hand, Khoo, Surienty and Selamat [21] determined a significant relationship between supervisor's support on safety and safety behavior in manufacturing sector.…”
Section: Introductionmentioning
confidence: 99%